POTENSI SELADA LAUT (Ulva Lactuca L.) SEBAGAI ANTIBAKTERI, ANTIINFLAMASI, DAN ANTIOKSIDAN DALAM TERAPI ACNE VULGARIS - Amritha Dewi, Luh Putu Widya; Kusuma Dewi, Kadek Yuma (Essence of Scientific Medical Journal; Vol 21 No 1 (2023): Volume 21 No. 1 (Januari - Juni 2023) Essential: Essence of Scientific Medical Journal, 2023)
Introduction: Acne vulgaris is a disorder of the pilosebaceous unit that has a high prevalence in the general population, especially in adolescents. In some cases, Acne vulgaris can form scar tissue which has the potential to cause a decrease in quality of life to psychological disorders. The use of antibiotics as a therapy for Acne Vulgaris is currently not completely satisfactory and safe because it can cause resistance, especially to Staphylococcus Aureus. Therefore, the use of herbal medicine can be a promising solution Discussion: Ulva lactuca L is one of the natural ingredients that can be used in the treatment of Acne Vulgaris because it has bioactive ingredients that act as antibacterial, anti-inflammatory and antioxidant. The antibacterial activity produced by the combination of Ulva lactuca L. metabolites reaches a concentration of 750 ppm and the activity of inhibiting the growth of S. aureus bacteria has a strong to very strong grade. The largest diameter of the inhibition zone was obtained at a concentration of 100% which was 22 ± 0.577 mm. As an anti-inflammatory, the content of flavonoids and carotenoids in Ulva lactuca L. can prevent the synthesis of pro-inflammatory mediators and neutralize free radicals. In addition, the IC50 result from testing using the DPPH method of Ulva Lactuca L. was 60.975 ppm which indicated that its antioxidant activity was relatively strong. The active ingredient Ulva Lactuca L. which is appropriate for treating Acne vulgaris is a gel with 3% hydroxypropyl methylcellulose (HMPC) gelling agent. Conclusion: Extraction of Ulva lactuca L. in gel preparations has excellent potential as a therapy for Acne Vulgaris due to the content of saponins, flavonoids and triterpenoids, alkaloids, tocopherols, melatonin, tannins and carotenoid compounds in the form of astaxanthin, ?-carotene, fucoxanthin and lutein which are contained therein.